2018
DOI: 10.1128/iai.00674-18
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone Administration Disrupts Intestinal Homeostasis, Mediating Noninflammatory Proliferation and Dissemination of Commensal Enterococci

Abstract: Enterococci are Gram-positive commensals of the mammalian intestinal tract and harbor intrinsic resistance to broad-spectrum cephalosporins. Disruption of colonization resistance in humans by antibiotics allows enterococci to proliferate in the gut and cause disseminated infections. In this study, we used (EF)-colonized mice to study the dynamics of enterococci, commensal microbiota, and the host in response to systemic ceftriaxone administration. We found that the mouse model recapitulates intestinal prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 87 publications
(82 reference statements)
2
21
1
Order By: Relevance
“…Finally, the majority of studies have focused on susceptibility to infection with specific pathogens such as Clostridium difficile, enterococci spp., salmonella spp., EPE, etc. and not the overall impact on the microbiota [9,11,12,14,15].…”
Section: Discussionmentioning
confidence: 98%
“…Finally, the majority of studies have focused on susceptibility to infection with specific pathogens such as Clostridium difficile, enterococci spp., salmonella spp., EPE, etc. and not the overall impact on the microbiota [9,11,12,14,15].…”
Section: Discussionmentioning
confidence: 98%
“…In keeping with this conclusion, Chakraborty et al . recently reported that intestinal proliferation is required for translocation of enterococci upon ceftriaxone treatment 25 . Epidemiological studies have also reported an association between VRE intestinal domination and bloodstream infection 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, exposure to ceftriaxone did not affect TJ protein expression, fecal albumin, or permeability to FITC-dextran. 46 Oral antibiotics were shown to induce colonic goblet cell-associated antigen passages that enabled translocation of live bacteria to MLN, which continued for~5 days after antibiotic withdrawal. 47 Thus, antibiotics may disrupt colonization resistance and physiological homeostatic processes, allowing for transient dissemination of bacteria even without overt intestinal pathology.…”
Section: Induced Gut Barrier Disruption and Translocationmentioning
confidence: 99%
“…39 Overall, enterococci and lactobacilli appear to be predominant genera translocating under pathologic conditions. 46…”
Section: Spontaneous Gut Commensal Disseminationmentioning
confidence: 99%